Relapsing De Novo Membranous Nephropathy. (2nd May 2022) - Ali, Ala; Al-Taee, Huda; Kadhim, Thaer J.
Abstract : Allograft membranous glomerulopathy can be a recurrent or de novo disease. Both instead have different underlying immune pathophysiology and disease pattern. While the introduction of ANTI-PLAR2 and THS7A brought new insights into the management of Immune/primary MN, the treatment of de novo MN is not clear. Relapsing de novo MN in a kidney transplant was rarely reported. Here, we present a case of relapsing de novo MN without evidence of rejection and a gratifying response to rituximab.